Student Motivation and Learning Interest in Virtual Laboratory-Based Instruction: A Literature Study (2016–2025) - Tiara Dwi Saiva; M Fadhil Khairullah; Siti Nurlali; Gunawan Gunawan; Nina Nisrina (Indonesian, 2026)
Virtual laboratory-based learning is rapidly expanding to overcome practical facility limitations and meet technological demands. Although its effectiveness is widely researched, most studies focus on cognitive aspects, leaving comprehensive syntheses regarding its impact on student motivation and interest limited. This literature review aims to analyze this influence thoroughly. Selecting 7 credible scientific articles from 2016–2025, the study utilizes content analysis and thematic synthesis to identify finding patterns. Results demonstrate that virtual laboratories consistently boost student motivation and interest through three key aspects: interactive visuals enhancing engagement, flexible access supporting independent learning, and simulation experiences fostering curiosity. This effectiveness depends heavily on instructional design and teachers' pedagogical integration of technology. In conclusion, virtual laboratories serve not only as a facility alternative but also as a strategic medium to enhance students' affective domain, offering conceptual contributions to technology-based learning development focused on student engagement and experience.